Long Term Osmotic Mini Pump Treatment with Alpha-MSH Improves Myocardial Function in Zucker Diabetic Fatty Rats - Szokol, Miklos (Molecules, 2017)
The present investigation evaluates the cardiovascular effects of the anorexigenic mediator alpha-melanocyte stimulating hormone (MSH), in a rat model of type 2 diabetes. Osmotic mini pumps delivering MSH or vehicle, for 6 weeks, were surgically implanted in Zucker Diabetic Fatty (ZDF) rats. Serum parameters, blood pressure, and weight gain were monitored along with oral glucose tolerance (OGTT). Echocardiography was conducted and, following sacrifice, the effects of treatment on ischemia/reperfusion cardiac injury were assessed using the isolated working heart method. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity was measured to evaluate levels of oxidative stress, and force measurements were performed on isolated cardiomyocytes to determine calcium sensitivity, active tension and myofilament co-operation. Vascular status was also evaluated on isolated arterioles using a contractile force measurement setup. The echocardiographic parameters ejection fraction (EF), fractional shortening (FS), isovolumetric relaxation time (IVRT), mitral annular plane systolic excursion (MAPSE), and Tei-index were significantly better in the MSH-treated group compared to ZDF controls. Isolated working heart aortic and coronary flow was increased in treated rats, and higher Hill coefficient indicated better myofilament co-operation in the MSH-treated group. We conclude that MSH improves global heart functions in ZDF rats, but these effects are not related to the vascular status.